Growth and reduction of cost of production of Pangasius hypophthalmus (Sauvage, 1878) with alternate feeding schedules - Ali, M Z; Haque, M K I; Parveen, R; Hussain, M G; Mazid, M A (Indian Journal of Fisheries, 2011)
A feeding trial was conducted in pond condition to investigate the effect of alternate feeding schedules on the growth and production cost of Thai pangas, Pangasius hypophthalmus. Ten experimental ponds each of 400 m2 size were divided into 5 treatment groups each with two replicates. Fish (5.3 + 0.6 gaverage weight) were stocked at the rate of 1,000 per pond (25,000/ha). High protein (30%, H) and low protein (15%, L) diets were prepared using locally available ingredients. Five different feeding schedules employed were: high protein diet (30% protein, H, low protein (15% protein, L) diet, 1 day low protein diet followed by 1 day high protein diet (1L/1H), 2 days low protein diet followed by 2 days high protein diet (2L/2H) and 7 days low protein diet followed by 7 days high protein diet (7L/7H). The fish were fed twice daily at the rate of 15, 10, 8 and 5% of their body weight for the 1st, 2nd, 3rd and 5thmonths respectively. Significantly (P